PENGARUH KEPEMIMPINAN KEPALA DESA TERHADAP PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA PELANDUK KECAMATAN MANDAH - Satar; SM Guntur; Bayu Fajar Susanto (Indragiri Research Center (ingreat), 2026)
This study aims to examine the influence of village head leadership on community participation in the development of Pelanduk Village, Mandah District. This research employs a qualitative approach with data collection techniques consisting of questionnaires, observation, and documentation. The population of this study includes the entire community of Pelanduk Village, totaling 2,888 people, with a sample of 44 respondents determined using the Slovin formula with a 15% margin of error. Data analysis was conducted using descriptive qualitative analysis by interpreting questionnaire results based on the Likert scale. The results indicate that the leadership of the village head in Pelanduk Village is categorized as good, as reflected in responsibility, communication, motivation, exemplary behavior, and community involvement in decision-making. Furthermore, community participation in village development is also categorized as good, particularly in terms of mutual cooperation and direct involvement in development activities. However, participation in financial contributions remains relatively low. This study concludes that village head leadership has a significant influence on community participation in village development. Effective, communicative, and participatory leadership enhances community involvement in village development programs.